FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MUZZAKI DALAM PEMBAYARAN ZAKAT ONLINE PADA LAZNAS DJALALUDDIN PANE FOUNDATION ( DPF ) KOTA MEDAN - Ginting, Adam Septyo; Dahrani, Dahrani (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the factors that influence muzzaki's interest in paying zakat online at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City. In this research, this research uses a trust transparency variable approach to muzakki's interest. The sample selection method in this study used a saturated sampling technique where the sample in this study consisted of 20 muzzaki at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City. The research results show that the transparency variable partially has a positive effect on muzzaki's interest in paying zakat online at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City with a significance of 0.003, which is below the criterion figure of 0.05. The trust variable partially has a positive effect on muzzaki's interest in paying zakat online at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City with a significance of 0.002, which is below the criterion figure of 0.05. The variables transparency and trust simultaneously have a positive effect on muzzaki's interest in paying zakat online at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City